Ag Nanoparticle‐Grafted PAN‐Nanohump Array Films with 3D High‐Density Hot Spots as Flexible and Reliable SERS Substrates. Issue 40 (27th August 2015) - Li, Zhongbo; Meng, Guowen; Huang, Qing; Hu, Xiaoye; He, Xuan; Tang, Haibin; Wang, Zhiwei; Li, Fadi
<x xml:space="preserve">Abstract</x> A facile fabrication approach of large‐scale flexible films is reported, with one surface side consisting of Ag‐nanoparticle (Ag‐NP) decorated polyacrylonitrile (PAN) nanohump (denoted as Ag‐NPs@PAN‐nanohump) arrays. This is achieved via molding PAN films with ordered nanohump arrays on one side and then sputtering much smaller Ag‐NPs onto each of the PAN‐nanohumps. Surface‐enhanced Raman scattering (SERS) activity of the Ag‐NPs@PAN‐nanohump array films can be improved by curving the flexible PAN film with ordered nanohump arrays during the Ag‐sputtering process to increase the density of the Ag‐NPs on the sidewalls of the PAN‐nanohumps. More 3D hot spots are thus achieved on a large‐scale. The Ag‐NPs@PAN‐nanohump array films show high SERS activity with good Raman signal reproducibility for Rhodamine 6G probe molecules. To trial their practical application, the Ag‐NPs@PAN‐nanohump array films are employed as SERS substrates for trace detection of trinitrotoluene and a congener of polychlorinated biphenyls. A lower detection limit of 10−12m and 10−5m can be achieved, respectively. Furthermore, the flexible Ag‐NPs@PAN‐nanohump array films can also be utilized as swabs to probe traces of methyl parathion on the surface of fruits such as apples. The as‐fabricated SERS substrates therefore have promising potential for applications in rapid safety inspection and environmental protection.